Trends in Age of Cochlear Implant Recipients, and the Impact on Perioperative Complication Rates. Issue 4 (April 2020) - Fakurnejad, Shayan; Vail, Daniel; Song, Yohan; Alyono, Jennifer; Blevins, Nikolas H.
Abstract : Objective: The aim of the study is to examine trends in the age of patients receiving cochlear implants and to determine the effect of age on the rate of perioperative complications. Study Design: Retrospective analysis of deidentified administrative claims data from a US commercial insurance database (Optum). Patients: Individuals undergoing cochlear implantation between 2003 and 2016. Setting: US hospital and outpatient facilities serving commercially insured patients. Intervention: Cochlear implantation. Main Outcome Measures: Age at implantation, incidence of perioperative complications within 30 days identified by ICD9/10 codes including device problems, myocardial infarction, stroke, venous thromboembolism, local infection, meningitis, stroke, cerebrospinal fluid leak, and facial weakness. Results: Between 2003 and 2016, 3420 patients underwent a total of 4154 cochlear implants. The number of implants per year increased annually from 171 in 2003 to 531 in 2016, with the greatest growth demonstrated in those aged 60 and older. The age of patients undergoing implantation increased annually from an average of 26.6–57.2 years ( p < 0.001). The implantation rates from 2003 to 2016, per 100, 000 enrollees, increased from 1.64 to 6.82 for patients 60–79 years of age, and 0 to 11.57 for patients greater than 80 years of age ( p < 0.001). No significant differences in 30-day complication rates were found between patients when grouped by age in decades, except for device related problems, which was significantly higher in younger patients (<18 years). Conclusion: Over the past decade and a half, cochlear implantation is more frequently being performed, and in an increasingly aging population. This trend does not seem to alter the risk of perioperative complications. Abstract : Supplemental Digital Content is available in the text